Workplace Stress and Teachers’ Productivity: An Empirical Evidence from Private College Teachers of Nepal (Far Western Review, 2025)
This research offers solid empirical evidence to support the existing literature, especially regarding teacher efficiency and its impact on student outcomes. The results reveal that various institutional factors have a notable influence on teacher performance. In particular, unfavorable working conditions, excessive workloads, student misconduct, and insufficient administrative support were identified as key contributors to decreased effectiveness. Among these, poor working conditions had the strongest impact. Interestingly, low incentives did not show a statistically significant effect, which could be attributed to specific contextual factors or coping mechanisms adopted by teachers. While the study captures most of the relevant indicators, some may have been overlooked, leaving room for future investigation. Researchers are encouraged to explore these remaining aspects and consider conducting similar studies with a broader geographical scope, as this research is limited to private colleges within the Kathmandu Valley.